1989
DOI: 10.1042/cs0760397
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cation transport in vivo in healthy volunteers after the oral administration of lithium carbonate

Abstract: 1. We have measured cation transport in vivo in seven healthy volunteers under control conditions and after they had taken lithium carbonate for 21 days in doses which maintained the serum lithium concentration in the range 0.6-0.8 mmol/l. 2. We have measured cation transport in vivo after the administration of an oral load of rubidium chloride, and have found that, although intra-erythrocytic concentrations of rubidium were significantly lower 1 h after the administration of rubidium when the subjects were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…It is also consistent with our previous finding that the activity of the Na+/K+ pump in vivo increased in the erythrocytes of healthy volunteers after 21 days of in vivo lithium administration (Wood et al, 1989b).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It is also consistent with our previous finding that the activity of the Na+/K+ pump in vivo increased in the erythrocytes of healthy volunteers after 21 days of in vivo lithium administration (Wood et al, 1989b).…”
Section: Discussionsupporting
confidence: 82%
“…Neither the results of our present ouabain binding experiment nor our previous in vivo Na+/K+ pump activity experiment (Wood et al, 1989b) is consistent with the earlier results of Naylor et al (1977). Those investigators demonstrated a small fall in Na+/K+ pumpmediated potassium uptake into erythrocytes ex vivo after lithium treatment, but no change in Na+,K+-ATPase activity, measured as the rate of hydrolysis of ATP.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Neuronal survival and degeneration after ischemia depends on the intracellular ATP supply and ion homeostasis (Martínez-Sánchez et al 2004). The strong edema-reducing effect of lithium reported here, more intense for the first 10 min of ischemia, can be a product of the stimulating action of lithium on Na/K-ATPase and MgATPase activities, which was reported in blood red cells (Glen et al 1972;Glen and Reading 1973;Dick et al 1974;Hesketh et al 1978;Wood et al 1989a), brain synaptosome Na/K-ATPase (Wood et al 1989b), or by increase in the number of Na/K-ATPases (Young 2009), but not by an increase in energy metabolites, as was shown by Lin et al (1993); thus, lithium can normalize abnormally elevated intracellular sodium levels induced by ouabain in human glioma cells (Huang et al 2007). Additionally, lithium selectively inhibits Na + influx through Na + channels and subsequent Ca 2+ influx and catecholamine secretion, independent of glycogen synthase kinase 3 inhibition (Yanagita et al 2007).…”
Section: Discussionmentioning
confidence: 76%